2014
DOI: 10.1163/1937240x-00002236
|View full text |Cite
|
Sign up to set email alerts
|

A rapid intertidal megafauna survey method applied to Upogebia pugettensis, and its introduced parasite, Orthione griffensis

Abstract: A B S T R A C TDeclines or extinctions of the native northeast Pacific intertidal blue mud shrimp, Upogebia pugettensis (Dana, 1852), over the species range are directly associated with intense infestations by the introduced Asian bopyrid isopod parasite, Orthione griffenis Markham, 2004. Single point sampling sites and anecdotal records poorly resolve how this interaction occurs within estuaries and among geographical regions. This broad scale interaction can only be resolved at the meta-population scales ove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…eschrichtii Complex IV sampling sites and WGW foraging ( Fig 1 ) by the field perimeters 2011 WGW sightings in 2011 [ 25 ]. We estimated the overlapping areas of these perimeters by polygon triangles summation using their geographical coordinates [ 59 ]. We produced all maps using open source software QGIS v. 2.12.1-Lyon ( http://qgis.org/ru/site/ ).…”
Section: Methodsmentioning
confidence: 99%
“…eschrichtii Complex IV sampling sites and WGW foraging ( Fig 1 ) by the field perimeters 2011 WGW sightings in 2011 [ 25 ]. We estimated the overlapping areas of these perimeters by polygon triangles summation using their geographical coordinates [ 59 ]. We produced all maps using open source software QGIS v. 2.12.1-Lyon ( http://qgis.org/ru/site/ ).…”
Section: Methodsmentioning
confidence: 99%
“…They are considered among the most influential ecosystem engineers in marine soft-bottom ecosystems [6,[10][11][12][13]. Their burrows not only expand into the sediment surface areas of estuaries and supply oxygenated water deep into subsurface sediments [14][15][16][17], but they also become microhabitats for various benthic animals and influence the structure of benthic communities in these habitats [18][19][20][21][22][23][24][25][26]. Additionally, their filter feeding improves water quality by capturing suspended particles, which in turn affects the coastal ecosystem and serves a vital ecological function [11,[27][28][29][30][31][32].…”
Section: Introductionmentioning
confidence: 99%
“…However, recently, this mud shrimp has mostly disappeared [36]. Dramatic declines in this native northeast Pacific mud shrimp over the past three decades have occurred in response to intense infestations by the Asian bopyrid isopod parasite, Orthione griffenis Markham, 2004 introduced in the 1980s [17,[36][37][38][39][40][41][42][43]. Making matters worse, the recent taxonomic review of Upogebia revealed a previously reported 1912 invasion of San Francisco Bay by Upogebia affinis (Say, 1818) that was in error; hence, the introduction of U. major is the first confirmed gebiid invasion in the world.…”
Section: Introductionmentioning
confidence: 99%
“…Mud shrimps are also host to the only documented case of an introduced epicaridean parasite Chapman et al 2012;Hong et al 2015). This parasite, Orthione griffenis Markham, 2004, has had profound impacts on populations of their ecosystem engineer hosts (Chapman & Carter 2014).…”
Section: Introductionmentioning
confidence: 99%